Estudo de viabilidade de substituição de facas rotativas em máquinas embaladoras através de análises de dados de vida - Manosso, Mariana Silveira (2017)
A company that manufactures health devices installed in Brazil has adopted as a competitive differential the cost reduction with maintenance parts of its equipment, provided that the primary quality of its products is maintained. The purpose of this study is to analyze the consumption of spare parts - slitter knives - in packaging machines. The methodology of the study allows the understanding of the system life data, using Reliability Engineering tools, through the Weibull distribution. Statistical analyzes were performed using Reliasoft software. A suggestion of alternative material for knife making and feasibility analysis of change is the proposed alternative to achieve cost reduction goals with maintenance expense at 10%. Results obtained through this study confirm the feasibility of the exchange of raw material for confection of rotary knives, whose alteration results in cost reduction of up to 45% with spare parts expenses.